Needs Analysis for English for Specific Purposes among Animation Students in a Vocational High School - Triska Priya Febriana; Diah Kurniati; Fitri Budi Suryani (SIMPLE: International Journal of English Education, 2026)
This study aims to analyze the English learning needs of Animation Study Program students at SMK Raden Umar Said Kudus in the context of English for Specific Purposes (ESP). Using a descriptive qualitative approach, data were collected through questionnaires, interviews with 10 students and one English teacher, and syllabus analysis. The needs analysis covered target needs (necessities, lacks, wants) and learning needs (motivation, methods, skills). Findings show that students have high motivation to learn English, primarily to support future careers in the animation industry, including aspirations to work internationally and master animation-specific terminology. Speaking emerged as the most needed skill (85%), followed by writing and vocabulary mastery, particularly technical terms in animation. However, many students reported difficulties in speaking fluently, pronunciation, and listening comprehension, indicating a gap between required and actual competencies. Syllabus analysis revealed that while the curriculum includes ESP-relevant topics such as procedure texts, descriptive texts, narrative texts, and CV writing, classroom implementation often focuses on general grammar and vocabulary with limited integration of animation-related content. Students prefer interactive, technology-based methods such as games, videos, and social media, and favor problem-based learning to connect English with real-world animation tasks. Teachers currently employ the PPP (Presentation, Practice, Production) method, but greater use of industry-specific materials and collaboration with animation instructors is recommended. The study concludes that stronger alignment of materials and methods with vocational contexts is essential to enhance students’ professional readiness in the global animation market.